A Surface Mediated Supramolecular Chiral Phenomenon for Recognition of l- and d-Cysteine - Wang, Jing (Nanomaterials (Basel), 2018)
Chiral recognition is of fundamental importance in chemistry and life sciences and the principle of chiral recognition is instructive in chiral separation and enantioselective catalysis. Non-chiral Ag nanoparticles (NPs) conjugated with chiral cysteine (Cys) molecules demonstrate strong circular dichroism (CD) responses in the UV range. The optical activities of the l-/d-Cys capped Ag NPs are associated with the formation of order arrangements of chiral molecules on the surface of Ag NPs, which are promoted by the electrostatic attraction and hydrogen bonding interaction. The intensity of the chiroptical response is related to the total surface area of Ag NPs in the colloidal solution. The anisotropy factor on the order of 10(−2) is acquired for Ag NPs with the size varying from ~2.4 to ~4.5 nm. We demonstrate a simple and effective method for the fabrication of a quantitative chiral sensing platform, in which mesoporous silica coated Ag nanoparticles (Ag@mSiO(2)) were used as chiral probes for recognition and quantification of Cys enantiomers.